Generation of mRx-Cre transgenic mouse line for efficient conditional gene deletion in early retinal progenitors - Klimova, Lucie; Lachova, Jitka; Machon, Ondrej; Sedlacek, Radislav; Kozmik, Zbynek (PloS one, 2013)
During mouse eye development, all retinal cell types are generated from the population of retina-committed progenitors originating from the neuroepithelium of the optic vesicle. Conditional gene inactivation provides an efficient tool for studying the genetic basis of the developing retina; however, the number of retina-specific Cre lines is limited. Here we report generation of the mRx-Cre BAC transgenic mouse line in which the expression of Cre recombinase is controlled by regulatory sequences of the mouse Rx gene, one of the earliest determinants of retinal development. When mRx-Cre transgenic mice were crossbred with the ROSA26R or ROSA26R-EYFP reporter lines, the Cre activity was observed in the optic sulcus from embryonic day 8.5 onwards and later in all progenitors residing in the neuroepithelium of the optic cup. Our results suggest that mRx-Cre provides a unique tool for functional genetic studies in very early stages of retinal development. Moreover, since eye organogenesis is dependent on the inductive signals between the optic vesicle and head surface ectoderm, the inductive ability of the optic vesicle can be analyzed using mRx-Cre transgenic mice.
Keywords: Eye Proteins; Recombination, Genetic; těhotenství; kmenové buňky; myši transgenní; retina; oční proteiny; Stem Cells; genetické inženýrství; Time Factors; zvířata; Animals; rekombinace genetická; časové faktory; Female; myši; Mice, Transgenic; Pregnancy; Integrases; Genetic Engineering; homeodoménové proteiny; ženské pohlaví; Mice; Retina; integrasy; delece genu; Gene Deletion; Homeodomain Proteins